2010
DOI: 10.1021/pr100034f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics of Salt Tolerance in Arabidopsis thaliana and Thellungiella halophila

Abstract: Salinity is a major abiotic stress affecting plant cultivation and productivity. Thellungiella halophila is a halophyte and has been used as a model for studying plant salt tolerance. Understanding the molecular mechanisms of salinity tolerance will facilitate the generation of salt tolerant crops. Here we report comparative leaf proteomics of Arabidopsis, a glycophyte, and its close relative Thellungiella, a halophyte, under different salt stress conditions. Proteins from control and NaCl treated Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
249
3
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(289 citation statements)
references
References 95 publications
27
249
3
10
Order By: Relevance
“…This technique is now widely applied to plants to understand changes in protein profiles during growth or due to environmental stimuli and stress (Lü cker et al, 2009;Schneider et al, 2009;Pang et al, 2010). However, few studies have directly evaluated the physiological importance of proteins identified by iTRAQ analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This technique is now widely applied to plants to understand changes in protein profiles during growth or due to environmental stimuli and stress (Lü cker et al, 2009;Schneider et al, 2009;Pang et al, 2010). However, few studies have directly evaluated the physiological importance of proteins identified by iTRAQ analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics studies revealed that the expression of many components of protein synthesis machinery are altered under salt stress conditions and suggested that protein synthesis plays a vital role in abiotic stress adaptation Witzel et al 2009;Pang et al 2010). Our study demonstrated that serine carboxypeptidase (spot 181) and pollen allergen MetE (spot 717),respectively related to protein processing and amino acid metabolism were down-regulated under salt stress.…”
Section: Protein Processing and Amino Acid Metabolismmentioning
confidence: 60%
“…There, reduction in abundance of RubisCo large/small subunit, chloroplast precursor (OEE), Oxygen-evolving enhancer protein 2, carbonic anhydrases as well as Rubisco's activity leads to short assimilation. Fall in assimilation has been reported for many glycophyte plants subjected to salinity stress (Aghaei, 2008; Pang et al, 2010;Sobhanian et al, 2010;Chatlopadhyay 2011 andBandehagh et al, 2011). However, in some sensitive plants, including durum wheat, an increase in activity of RubisCo is thought to be a response rendered to support the carboxylase activities of RubisCo (Caruso et al, 2008).…”
Section: Protein Identificationmentioning
confidence: 99%